2016
DOI: 10.1016/j.biopsych.2016.03.2101
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Increases Prefrontal Inhibition: A Mechanism for Stress-Induced Prefrontal Dysfunction

Abstract: Background Multiple neuropsychiatric disorders, e.g., depression, are linked to imbalances in excitatory and inhibitory neurotransmission and prefrontal cortical dysfunction, and are concomitant with chronic stress. Methods We used electrophysiologic (n = 5–6 animals, 21–25 cells/group), neuroanatomic (n = 6–8/group), and behavioral (n = 12/group) techniques to test the hypothesis that chronic stress increases inhibition of medial prefrontal cortex (mPFC) glutamatergic output neurons. Results Using patch c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
141
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(154 citation statements)
references
References 94 publications
(78 reference statements)
10
141
3
Order By: Relevance
“…In children, neuroendocrine markers of stress and adversity at baseline (i.e., high cortisol) are predictive of smaller amygdala and hippocampal volumes and cognitive functioning (31, 32). The neurological sequelae of chronic stress is considered diffuse (33), consistent with the present and prior findings where high VS resulted in greater decline in global cognitive functioning and more than doubled the risk of clinical and neuropathological confirmed dementia (34). There may also be a threshold to which VS must cross to influence cognitive decline in LLD.…”
Section: Resultssupporting
confidence: 89%
“…In children, neuroendocrine markers of stress and adversity at baseline (i.e., high cortisol) are predictive of smaller amygdala and hippocampal volumes and cognitive functioning (31, 32). The neurological sequelae of chronic stress is considered diffuse (33), consistent with the present and prior findings where high VS resulted in greater decline in global cognitive functioning and more than doubled the risk of clinical and neuropathological confirmed dementia (34). There may also be a threshold to which VS must cross to influence cognitive decline in LLD.…”
Section: Resultssupporting
confidence: 89%
“…mPFC GR suppression was also reported following non-alcohol-related chronic stress (McKlveen et al, 2016), suggesting that the mPFC GR suppression reported herein may be a manifestation of chronic HPA-axis activation, perhaps engaging opponent (e.g., desensitization, tolerance) mechanisms in the mPFC. Mifepristone, a GR antagonist, may inhibit the effects of chronically elevated CORT on such compensatory processes in the mPFC, leading to a relative increase in GR expression and function compared to placebo groups.…”
Section: Discussionsupporting
confidence: 65%
“…These mismatches suggests that the GR-mediated effects on ethanol self-administration (also) involve regions other than the mPFC, perhaps the nucleus accumbens and ventral tegmental area (Repunte-Canonigo et al, 2015). Instead, mPFC GR changes may contribute to other stress-related behaviors (McKlveen et al, 2016; Myers et al, 2014). Our study also shows similar changes in plasma peak CORT levels in CIE-ED and ED rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lentiviral knockdown of GR in the IL (but not prelimbic cortex) produces a marked potentiation of HPA axis and PVN Fos induction to a novel stress in animals exposed to CVS (91), a phenomenon linked to interneuron-mediated decreases in IL output (92). Implants of the GR antagonist mifepristone in the NTS inhibit PVN excitability following chronic stress, suggesting that the glucocorticoids may play a role in inhibiting the NTS drive to the PVN (93).…”
Section: Chronic Stress and Pvn Afferentsmentioning
confidence: 99%